Blood Pressure– and Coronary Perfusion Pressure–Targeted Cardiopulmonary Resuscitation Improves 24-Hour Survival From Ventricular Fibrillation Cardiac Arrest. Issue 11 (November 2016) - Naim, Maryam Y.; Sutton, Robert M.; Friess, Stuart H.; Bratinov, George; Bhalala, Utpal; Kilbaugh, Todd J.; Lampe, Joshua W.; Nadkarni, Vinay M.; Becker, Lance B.; Berg, Robert A.
Abstract : Objectives: Treatment algorithms for cardiac arrest are rescuer centric and vary little from patient to patient. The objective of this study was to determine if cardiopulmonary resuscitation–targeted to arterial blood pressure and coronary perfusion pressure rather than optimal guideline care would improve 24-hour survival in a porcine model of ventricular fibrillation cardiac arrest. Data Sources: Preclinical animal laboratory using female 3-month-old swine. Study Selection: A randomized interventional study. Data Extraction: After induction of anesthesia and 7 minutes of untreated ventricular fibrillation, 16 female 3-month-old swine were randomized to 1) blood pressure care: titration of chest compression depth to a systolic blood pressure of 100 mm Hg and vasopressor dosing to maintain coronary perfusion pressure of greater than 20 mm Hg or 2) guideline care: chest compression depth targeted to 51 mm and standard guideline vasopressor dosing. Animals received manual cardiopulmonary resuscitation for 10 minutes before the first defibrillation attempt and standardized postresuscitation care for 24 hours. Data Synthesis: Twenty-four–hour survival was more likely with blood pressure care versus guideline care (0/8 vs 5/8; p < 0.03), and all survivors had normal neurologic examinations. Mean coronary perfusion pressure prior to defibrillation was significantly higher with blood pressure care (28 ± 3 vs 10 ± 6 mm Hg; p < 0.01). Chest compression depth was lower with blood pressure care (48 ± 0.4 vs 44 ± 0.5 mm Hg; p < 0.05), and the number of vasopressor doses was higher with blood pressure care (median, 3 [range, 1–7] vs 2 [range, 2–2]; p < 0.01). Conclusions: Individualized goal-directed hemodynamic resuscitation targeting systolic blood pressure of 100 mm Hg and coronary perfusion pressure of greater than 20 mm Hg improved 24-hour survival compared with guideline care in this model of ventricular fibrillation cardiac arrest.